Praise indeed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The director of the Livestock Agricultural Project in Kembolcha, Ethiopia,Mohamed Yimer, tells of 'our rural community which is very removed and where there is no extension agent or man to provide information on agricultural techniques. The...